EKSTRAK DAUN PANDAN WANGI DAN ASAM JAWA TERHADAP DAYA REPELEN NYAMUK Aedes aegypti - Wintah, Wintah; Kiswanto, Kiswanto (BAPPEDA Kota Pekalongan, 2019)
There are some plants that have a distinctive odor and which smell is not liked by mosquitoes. one of the plants that is easily obtained and doubly beneficial for humans is pandan wangi leaves (pandanus amaryllifolius oxb) and tamarind leaves. The purpose of this study was to determine the effect of acidic extract of tamarind leaves on Aedes aegypti mosquitoes at various concentrations and the effect of persistence (length of time) of tamarind leaf extract applied on the test of Aedes aegypti mosquito, the method used is the experimental method, which is testing pandan wangi leaf extract and tamarind leaves with various concentrations on mosquito control. So the design used is a Completely Randomized Design (CRD). The results showed that essential oils of pandan wangi leaves and tamarind leaves had an effect on the repellent power of Aedes aegypti mosquitoes at 07.00-10.00 WIB and at 15.00-17.00 WIB. At the observations at 07.00-10.00 WIB, giving the most fragrant pandan leaves oil at concentrations of 50% and 90% with expulsion power of 89.7% and 91.3%. Whereas in the observation at 15.00-17.00 WIB the use of essential oils of pandan wangi leaves expelled the mosquitoes at a concentration of 70% with an expulsion of 89.3%, and the mosquito acid of the mosquitoes which was displaced by 89%. The next suggestion is to use other plants besides pandan wangi and tamarind leaves which are not widely used to control mosquitoes, especially mosquitoes that can cause diseases such as Aedes aegypti. Keywords: Pandan wangi, Tamarind, Repellent, Mosquitoes